Growth of the service sector in the Yangtze River Delta - Liu, Zhibiao 1959-; Zheng, Jianghuai 1968- (Enrich series on China's economic issues, 2011)
The shift in economic development to the fast-rising industrial value chain is regarded as the key to the future of the Yangtze River Delta (YRD). This book provides a long-term study of the economic growth of the YRD. It compares the region's previous importance with its present economic growth, structural change and institutional reform. The book also provides detailed institutional and empirical studies on the fast rising value chain, the mode of development, mechanisms, behavior and performance of the modern service sector in the YRD.